The Role of Essay Writing Course, Given along with Comprehension-based Instruction, on the Writing Skill Development of High School Students - Secer, Sule Yuksel Ertugrul; Celikoz, Nadir (HACETTEPE UNIV, ELT DEPT, 2017)
This paper aims to analyze the effect of Essay Writing Course, given as specific writing skill instruction along with comprehension-based instruction, on the writing skill development of high school students. The paper is based on a quantitative study conducted in true experimental design. According to the Comprehension Hypothesis (Krashen, 1994, 2003), a comprehension-based instruction with an emphasis on reading and listening practice as receptive skills, will eventually lead to students' improvement in writing and speaking as productive skills, and to their overall language development. Besides, specific writing skill instruction and effective writing practices have a proven record of success in enhancing students' writing (Graham, 2018). Within the scope of this study, to determine if there is a meaningful difference in between the writing skill development of the students who take Essay Writing Course and of those who do not take any rhetorical course, apart from the comprehension-based instruction, the first and final writing exam scores and achievement levels of two groups of students are compared by a series of paired sample and independent t-tests, analyzed in SPSS and discussed in the scope of the study. It can be concluded from the results of the analysis that the experimental group, given the Essay Writing Course as writing skill instruction is significantly more successful than the control group, not given any writing skill instruction apart from comprehension oriented instruction. Within the analysis, done in the study, it can be also claimed that Essay Writing Course has a positive impact over the writing skill development of high school students. (C) 2017 EJAL & the Authors. Published by Eurasian Journal of Applied Linguistics (EJAL). This is an open-access article distributed under the terms and conditions of the Creative Commons Attribution license (CC BY-NC-ND).
Keywords: Writing skill; comprehension-based instruction; writing skill instruction; PERFORMANCE; LANGUAGE; Linguistics